2019
DOI: 10.1162/jocn_a_01362
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movements in the “Morris Maze” Spatial Working Memory Task Reveal Deficits in Strategic Planning

Abstract: Analysis of eye movements can provide insights into processes underlying performance of cognitive tasks. We recorded eye movements in healthy participants and people with idiopathic Parkinson disease during a token foraging task based on the spatial working memory component of the widely used Cambridge Neuropsychological Test Automated Battery. Participants selected boxes (using a mouse click) to reveal hidden tokens. Tokens were never hidden under a box where one had been found before, such that memory had to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…This has proven helpful not only for the TMT but a wide range of neuropsychological tests before (e.g. Corsi blocks, [ 42 ]; spatial working memory, [ 43 ]). Still, relating test scores to differences between the test halves leaves a lot of room for interpretation since both differ greatly in their cognitive demands and in turn their underlying cognitive functions.…”
Section: Introductionmentioning
confidence: 99%
“…This has proven helpful not only for the TMT but a wide range of neuropsychological tests before (e.g. Corsi blocks, [ 42 ]; spatial working memory, [ 43 ]). Still, relating test scores to differences between the test halves leaves a lot of room for interpretation since both differ greatly in their cognitive demands and in turn their underlying cognitive functions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with patients with PD can also help highlight important relationships between eye movements and working memory performance. Hodgson et al (2019) recorded eye movements in people with PD and in controls during the execution of a variation of a working memory task. Participants were required to search for reward tokens among identical square icons presented in different spatial locations on a monitor.…”
Section: Deficits In Search Behaviourmentioning
confidence: 99%
“…Although there is some inconsistency in the literature concerning whether antisaccade errors are increased in PD, the majority of studies report significantly increased directional errors in the task (Antoniades and Kennard 2015 ; Chan et al 2005 ; Briand et al 1999 ; Fukushima et al 1994 ; although see Lueck et al 1990 ; Rivaud et al 2007 ). In our experience there is considerable heterogeneity between Parkinson's patients with respect to antisaccade errors, perhaps reflecting different neurological trajectories of disease progression, which may in part explain why some studies have not shown significant increases in errors at the group level in patients (Hodgson et al 2019 ). The present results confirmed that as a group, given sufficient sample size, patients with mild to moderately severe symptoms have significantly increased directional errors in the antisaccade test as well as longer SRTs.…”
Section: Discussionmentioning
confidence: 91%
“…This suggestion, that PDs have difficulty resolving the distracting influence of visuospatial cues, is also consistent with the wider literature on attention and cognitive functioning in Parkinson's. Patients with Parkinson's appear to be more susceptible to distracting stimuli in visual and memory-guided search tasks (Mannan et al 2008 ; Hodgson et al 2019 ); irrelevant stimuli during task switching, at least when in an unmedicated state (Cools et al 2001 ); and the ability to suppress actions compatible with stimulus location in a “simon effect” task (Praamstra and Platt 2001 ). Difficulty in suppressing the influence of the cues on response selection mechanisms is also consistent with the greater influence of directional cues on saccades shown by patients in the spatial cueing task.…”
Section: Discussionmentioning
confidence: 99%